Propolis mitigates histopathological alterations in the pituitary gland and reproductive system of female albino rats subjected to cadmium toxicity - Abdulla A. Albishtue; Aqeel Mohsin Al-Mahmmodi; Hasan A. Almamoori; Mustafa Ali Alahmer (Veterinary World)
Background and Aim: Cadmium (Cd) is a pervasive environmental toxin that disrupts endocrine function and induces oxidative damage in reproductive organs. Propolis (PRO), a resinous substance produced by bees, has garnered attention for its antioxidant and estrogenic properties. This study investigated the protective potential of PRO on the pituitary-ovarian-uterine axis in female rats subjected to Cd-induced toxicity.